HIV-1 protease processes procaspase 8 to cause mitochondrial release of cytochrome c, caspase cleavage and nuclear fragmentation - Nie, Zelin; Krammer, Peter H. (Cell death and differentiation, 2002)
Infection of T cells with HIV-1 induces apoptosis and modulates apoptosis regulatory molecules. Similar effects occur following treatment of cells with individual HIV-1 encoded proteins. While HIV-1 protease is known to be cytotoxic, little is known of its effect on apoptosis and apoptosis regulatory molecules. The ability of HIV-1 protease to kill cells, coupled with the degenerate substrate specificity of HIV-1 protease, suggests that HIV-1 protease may activate cellular factor(s) which, in turn, induce apoptosis. We demonstrate that HIV-1 protease directly cleaves and activates procaspase 8 in T cells which is associated with cleavage of BID, mitochondrial release of cytochrome c, activation of the downstream caspases 9 and 3, cleavage of DFF and PARP and, eventually, to nuclear condensation and DNA fragmentation that are characteristic of apoptosis. The effect of HIV-1 protease is not seen in T cell extracts which have undetectable levels of procaspase 8, indicating a specificity and requirement for procaspase 8.
Gesehen am 14.04.2021